Freedom to Learn Curriculum from Kiai Haji Hasyim Asy'ari's Perspective (A Study of Book Adab Al-’Alim wa Al-Muta'allim) (Program Studi Pendidikan Agama Islam, 2022)
This study aims to describe the freedom to learn policy with a portrait of independent learning contained in the book Adab Al-’Alim Wa Al-Muta’allim by Kiai Haji Hasyim Asy'ari. This study employed the method of literature study with a qualitative descriptive approach. The researchers used the book of Adab Al-’Alim Wa Al-Muta’allim as the main source. Then, it was analyzed with contextual analysis. The results of this study revealed the concept of the freedom to learn policy offered by Kiai Haji Hasyim Asy'ari, including: first, learning according to the field of science and competence. Second, independent learning activities aim to create a generation with loyalty, piety, noble character, more creativity, the ability to work together, global diversity, critical thinking, and independence characteristics. Third, Kiai Haji Hasyim Asy'ari also developed literacy potential by reviewing various reference materials. The fourth is improving the ability of educators. Further, this research is expected to strengthen the freedom to learn curriculum from the perspective of Islamic education leaders.